2012
DOI: 10.1061/(asce)em.1943-7889.0000396
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Probability Distribution of Strength of Quasibrittle Structures Failing at Macrocrack Initiation

Abstract: Engineering structures must be designed for an extremely low failure probability, P f < 10 À6 . To determine the corresponding structural strength, a mechanics-based probability distribution model is required. Recent studies have shown that quasibrittle structures that fail at the macrocrack initiation from a single representative volume element (RVE) can be statistically modeled as a finite chain of RVEs. It has further been demonstrated that, based on atomistic fracture mechanics and a statistical multiscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…(8) does not apply as D → 0, which makes sense because the continuum model breaks down for structures of very small size. A recent study (Le et al 2012) has shown that for small and intermediate-size structures the size effect derived from this finite weakest-link model with the use of elastic stresses agrees well with the prediction from the nonlinear deterministic calculation. This is because the mean size effect behavior for small-size and intermediate-size structures is mainly caused by the operative stress redistribution mechanism, which can be well predicted by a nonlinear deterministic calculation.…”
Section: Case Of Zero-stress Singularitysupporting
confidence: 56%
See 1 more Smart Citation
“…(8) does not apply as D → 0, which makes sense because the continuum model breaks down for structures of very small size. A recent study (Le et al 2012) has shown that for small and intermediate-size structures the size effect derived from this finite weakest-link model with the use of elastic stresses agrees well with the prediction from the nonlinear deterministic calculation. This is because the mean size effect behavior for small-size and intermediate-size structures is mainly caused by the operative stress redistribution mechanism, which can be well predicted by a nonlinear deterministic calculation.…”
Section: Case Of Zero-stress Singularitysupporting
confidence: 56%
“…This is because the mean size effect behavior for small-size and intermediate-size structures is mainly caused by the operative stress redistribution mechanism, which can be well predicted by a nonlinear deterministic calculation. At the same time, this mechanism can also be captured by the finite weakest-link model, where the statistical multiscale transition model used for the formulation of the cdf of RVE strength consists of statistical bundles and chains that represent the damage localization and load redistribution mechanisms at different scales (albeit only the elastic stresses are used) (Le et al 2011(Le et al , 2012. For large-size structures, the zone of stress redistribution is negligible compared with the structure size, and the size effect is mainly caused by the randomness of material strength, which cannot be captured by the deterministic calculation.…”
Section: Case Of Zero-stress Singularitymentioning
confidence: 99%
“…The slip led to a vertical crack in the 8 m thick shell of the arch of the dam, and the statistical Type 1 size effect must have come into play. The conclusion from the analysis in [29,125] (improving on [126]) is that the tolerable abutment displacement should have been one half of that considered in design, which was at a time when the size effect was unknown.…”
Section: Some Ramifications and Structural Engineering Applicationsmentioning
confidence: 99%
“…The failure state for the arch can simply be written as σ N − σ L < 0. Previous studies [11,25] led to the following parameters for the RVE strength distribution of concrete: m = 24, s 0 = 2.12 MPa, µ G = 2.91 MPa, δ G = 0.44 MPa, ω = 0.15, and a RVE size of 280 mm. However, the cdf of σ L , which is determined by the statistics of abutment movement, is currently not available.…”
Section: Abutment Movementmentioning
confidence: 99%